HUBUNGAN DUKUNGAN KELUARGA DENGAN KEPATUHAN PENGGUNAAN INSULIN PADA PASIEN DIABETES MELITUS TIPE 2 DI PUSKESMAS KECAMATAN MATRAMAN JAKARTA TIMUR TAHUN 2023 - Amalia Nur Hasanah, Nafa; Siswandi, Iyar (JURNAL KESEHATAN KARTIKA, 2024)
Background: Diabetes mellitus is a metabolic disorder that occurs chronically or chronically because the body does not have enough insulin due to impaired insulin secretion, insulin hormones that do not work properly or both and if not compliant in treatment, acute complications can occur. Objective: to determine the relationship between family support and adherence to insulin use in patients with type 2 diabetes mellitus at the Matraman District Health Center, East Jakarta in 2023. Methods: The type of research used in this study is descriptive correlation using a cross sectional approach. The population in this study were type 2 Diabetes Mellitus patients who used insulin, namely 30 people and the sample used total sampling. Family support questionnaire using HDFSS and compliance using MMAS. Results Univariate analysis showed 73.3% of respondents had good family support and 26.7% of respondents had less family support. Bivariate analysis using the Chi-square test is that there is a relationship between family support and stress levels with a p-value (0.022). Conclusion there is a relationship between family support and compliance with insulin use in patients with type 2 diabetes mellitus at the Matraman District Health Center, East Jakarta in 2023.